2014
DOI: 10.1542/peds.2013-3169
|View full text |Cite
|
Sign up to set email alerts
|

Strength Capacity and Cardiometabolic Risk Clustering in Adolescents

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Resistance exercise is known to have a robust effect on glycemic control and cardiometabolic health among children and adolescents, even in the absence of weight loss. WHAT THIS STUDY ADDS:Normalized strength capacity is associated with lower cardiometabolic risk clustering in boys and girls, even after adjustment for cardiorespiratory fitness, level of physical activity, and BMI. abstract OBJECTIVES: The purpose of this study was to determine the genderspecific independent associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 40 publications
3
45
1
3
Order By: Relevance
“…42,43 Notably, we found significant intervention effects for upper body muscular endurance and RT skill competency. The intervention activities were predominantly resistance-based and as such focused on developing muscular fitness.…”
Section: Discussionmentioning
confidence: 68%
“…42,43 Notably, we found significant intervention effects for upper body muscular endurance and RT skill competency. The intervention activities were predominantly resistance-based and as such focused on developing muscular fitness.…”
Section: Discussionmentioning
confidence: 68%
“…Nevertheless, in a study of more than 1 million adolescent boys, low muscular strength was a primary risk factor for major causes of death, such as cardiovascular diseases, and effect sizes were equivalent to those of established risk factors such as elevated BMI. 9 Moreover, we and others have shown a robust, independent association between low strength and cardiometabolic risk clustering among adolescents 1013 —reiterating the need for improved clinical screening strategies across all ages. This is only feasible if population-based growth charts of strength are readily available to clinicians.…”
Section: Introductionmentioning
confidence: 55%
“…Two very recent studies from the Baltimore Longitudinal Study of Aging (BLSA) have demonstrated that greater adiposity [13] and chronic hyperglycemia [14] (i.e., two hallmark features of diabetes) are associated with persistently lower muscle quality and strength, respectively, and that these secondary consequences may be mediated by neurological factors such as neuropathy. We and others have shown an independent, inverse association between low strength and cardiometabolic risk clustering even among adolescents [1517]-reiterating the need for early and improved clinical screening strategies across populations. Therefore, the purposes of this study were to examine the independent association between handgrip strength capacity and diabetes in a large, nationally-representative sample, and to explore potential age- and sex-specific thresholds of weakness, for optimal risk categorization.…”
Section: Introductionmentioning
confidence: 81%